An Anisotropic Dielectric Elastomer Actuator with an Oriented Electrospun Nanofiber Composite Film. Issue 8 (29th January 2023) - Zhang, Yang; Chen, Zhiwen; Xu, Feng; Lin, Jiawei; Zhu, Bin; Xu, Zhenjin; Zhou, Gang; Zhang, Shaohua; Chen, Qinnan; Wang, Lingyun; Wu, Dezhi
Abstract: Anisotropic actuation, a universal phenomenon in nature, may be inspiring for the development of intelligent soft robotics in the future. For dielectric elastomers (DEs), important investigations have been done to decrease the voltage and increase the actuation strain. However, mechanical isotropy of synthetic DEs shows in‐plane uniform deformation, lacking the controllability of the actuation direction. Herein, an anisotropic DE (denoted as ADE) is constructed by casting Ecoflex/BaTiO3 solution onto oriented TPU nanofibrous membranes fabricated via drum electrospinning. The resulting ADE with a seamless three‐layer structure features mechanical anisotropy in the elastic modulus, with the maximum ratio between x and y directions of the plane being 11. A prototype ADE‐based actuator demonstrates a high electroactuation anisotropy of 3.95, a large unidirectional length strain of 15%, and a high energy density of 0.014 MJ m −3 at an electric field of 40 V µm −1 . Two potential applications, a flow divider valve simulating the Transwell test in the medical field and a mechanical stimulus component mimicking the maturation of cardiomyocytes, are successfully demonstrated. Thus, this work offers a versatile yet simple approach for fabricating anisotropic electroactive elastomer actuators in the future. Abstract : This paper introduces an anisotropic dielectric elastomer (ADE) by pouring the Ecoflex/BaTiO3 solution onto oriented TPU nanofibrous membranes. An ADE‐based actuator shows an electroactuation anisotropy of 3.95, a unidirectional length strain of 15%, and an energy density of 0.014 MJ m −3 at an electric field of 40 V µm −1 . This work offers some potential applications in the biomedical field.